Шелковые слова: роман / Сандра Браун ; [перевод с англ. Е. Тюрниковой] - Браун Сандра (Наслаждение, 1998)
Экземпляры: Ф. 10 (20200610) / Инвентарный номер: 47824 / Цена: 42.00 / Сис.шифр: 84(7Coe) / Авт.знак: Б 87 / ГРНТИ: 17.82 / ББК: 84(7Coe)